Economic Tyranny in Ancient, Medieval and Modern Egyptian Civilization - Saadoun Abdul Hadi Barghash Al-Amir, Prof. Dr. (lark, 2025)
The agricultural ages in prehistoric Egypt developed naturally. Over time, particularly with the advent of the Neolithic era, the ancient Egyptian learned how to cultivate and farm his land. He planted certain crops by sowing seeds into the silt left behind after the Nile’s floodwaters receded, allowing them to grow until harvest time. He began using simple primitive tools such as the axe and sickle, which were made from flint stone. He also invented tools like the plow and the shaduf (water-lifting device) to irrigate his fields during the summer by raising water from the Nile. The ancient Egyptian cultivated various plants, some of which grew naturally. Agriculture came to hold a central role in Egypt’s economic life, highlighting the importance of the farmer, who worked the land and utilized it. He became the driving force behind the entire economic activity of the country. In fact, the farmer and the Nile together came to be seen as the two pillars upon which the nation’s wealth was built. Without the farmer, Egypt would surely have perished; for the Nile and the farmer are two complementary forces, and together they sustained Egyptian prosperity to this very day.